2021
DOI: 10.3390/ijms222212100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metallic and Carbon-Based Nanomaterials on Human Pancreatic Cancer Cell Lines AsPC-1 and BxPC-3

Abstract: Pancreatic cancer, due to its asymptomatic development and drug-resistance, is difficult to cure. As many metallic and carbon-based nanomaterials have shown anticancer properties, we decided to investigate their potential use as anticancer agents against human pancreatic adenocarcinoma. The objective of the study was to evaluate the toxic properties of the following nanomaterials: silver (Ag), gold (Au), platinum (Pt), graphene oxide (GO), diamond (ND), and fullerenol (C60(OH)40) against the cell lines BxPC-3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…More studies with clinical cases and experimental animals will be beneficial. AsPC-1 and BxPC-3 cell lines, derived from primary pancreatic cancer tumors and characterized by their diffuse and metastatic behavior, have been widely utilized as standard models to investigate gene function in numerous studies related to pancreatic cancer [51][52][53]. However, additional research is required to explore the use of other types of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…More studies with clinical cases and experimental animals will be beneficial. AsPC-1 and BxPC-3 cell lines, derived from primary pancreatic cancer tumors and characterized by their diffuse and metastatic behavior, have been widely utilized as standard models to investigate gene function in numerous studies related to pancreatic cancer [51][52][53]. However, additional research is required to explore the use of other types of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that altering the size, spatial structure, charge number and polarity of metallic nanomaterials, as well as modifying and functionalising them, can help to reduce their biotoxicity. [234][235][236][237] In addition, similar to other nanomaterials, metallic nanomaterials are highly susceptible to phagocytosis by the vascular endothelial system in the body, resulting in a significant reduction in the number of nanoparticles transported to the tumor region and thus a significant reduction in the effectiveness of tumor therapy. 238,239 However, most of the related research is still at the initial stage, and how to better reduce the biotoxicity of metal nanomaterials, as well as their stability in vivo and the accuracy of targeting delivery in the tumor region will be one of the future research priorities in the field of tumor therapy.…”
Section: Polymeric Metal Nanomaterialsmentioning
confidence: 99%
“…No toxicity effects were identified in mice organs with ML111-NPS alone, and with the combination there was a reduction of side effects associated with vincristine [ 155 ]. Besides, the use of a hydrolyzed galactomannan (hGM)-based amphiphilic NPS for selective intratumoral accumulation in pediatric sarcoma was also investigated [ 156 ]. Coupling of these NPS with the tyrosine kinase inhibitor imatinib could target glucose transporter-1 (GLUT-1), both in rhabdomyosarcoma cells and in EWS PDX with different GLUT-1 expression levels with a 7.5% of efficiency [ 157 ], which make them a potential tool against GLUT-1-expressing tumors.…”
Section: Nanotherapy: a Refined Target-specific Drug Delivery Systemmentioning
confidence: 99%
“…particles [ 146 ]. Metal-based NPS of gold and silver (Au and Ag NPS, respectively) have been reported to have antitumor effects [ 156 , 167 , 168 ]; however, Ag NPS can induce general toxicity in non-target organs [ 169 ]. These NPS have been also evaluated in the context of EWS at preclinical level.…”
Section: Nanotherapy: a Refined Target-specific Drug Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation